World Environmental and Water Resources Congress 2020 Nevada and California Water History - Ahmad, Sajjad (Civil engineer); Murray, Regan (American Society of Civil Engineers, 2020)
Selected papers from the World Environmental and Water Resources Congress 2020, held in Henderson, Nevada, May 17-21, 2020. Sponsored by the Environmental and Water Resources Institute of ASCE.This collection contains 15 peer-reviewed papers on Nevada and California water history.Topics include: the Grand Canyon Dam; Hoover Dam construction history; and the Boulder Dam.This proceedings will be of interest to practitioners and researchers in all areas of water resources engineering.
Keywords: Water resources development -- Nevada.; elektronické knihy; electronic books